(untitled) (Archive of Conferences, 2020)
In recent years, the great Uzbek poet and thinker Alisher Navoi has been the subject of much analysis in the press. However, this does not mean that everyone knows the personality of a great person. If we did not live at the same time as him, "How do we know his character?" The right question arises. In my article, I have tried to develop his own character by drawing conclusions from the writings of his teachers or peers who lived at the same time as him, and from the verses he wrote.